Monetary Control Procedures and Financial Reform : Approaches, Issues, and Recent Experiences in Developing Countries. (IMF Working Papers; Working Paper, 1989)
Many countries have initiated reforms in their monetary control procedures by relaxing direct controls and increasing the role of market processes. The changed approach is often inevitable when countries reform their financial systems in support of growth and adjustment. This is because reform of those procedures increases the scope of monetary policy for stabilization purposes and allows for more flexible arrangements for setting interest rates and allocating credit that are necessary elements in improving resource mobilization and the efficiency of investment. This paper discusses the approaches to reforming monetary instruments, the issues in implementation, and experiences in developing countries.